Neoadjuvant radiochemotherapy in squamous cell cancer of the esophagus – morphological assessment and clinical results - Bernacki, Andrzej; Nikliński, Jacek; Laudański, Jerzy; Furman, Krzysztof; Furman, Marian; Kozłowski, Mirosław; Kiluk, Stanisław (Contemporary Oncology/Współczesna Onkologia, 2000)
The study was perfomed in 37 pateints with squamous cell carcinoma of the esophagus in two groups. In group I – 12 patients received no preoperative treatment, in group II – in 25 patients preoperative concurrent radiotherapy (200 cGy/day to tatal dose of 3000 cGy) and chemotherapy (Cisplatin – on days 1 to 5 and 17 to 21 at a dose of 20 mg/m 2 /day and 5-Fluorouracyl continuous i. v. infusion of 300 mg/m 2 /day) were administered. In group II after operation in 4 patients microscopic examination revealed no presence of cancer cells – complete response (CR). Of twelve patients with reduction of neoplastic infiltration 7 had partial response 1 (PR1) and 5 had partial response 2 (PR2). In 7 patients no changes were detected – stable disease (SD). In clinical examination we assessed – stage of the disease (pTNM), postoperative complications and 2-years survival. 27% of the patients in group I and 48% of patients in group II survived 2 years after the operation. Conclusions: Neoadjuvant radiochemotherapy improves 2-years survival rate in squamous cell esophageal cancer. Long term clinical results correlate with the response of the tumour to the preoperative treatment.